Perancangan Aplikasi Perangkat Lunak Penghapus Folder Dengan Menggunakan Algoritma Network Security Agency (NSA) - Ritonga, Samsul Malik (STMIK Budi Darma, 2019)
Along with technological advances in various fields, as if there was never a death to learn it. From day to day technological advances continue to develop very rapidly which greatly affects human work and much of human work itself has been replaced by computer technology. On the Windows operating system, when deleting a file, the file is not completely erased. This file is only hidden by